Environment Intensifies Imbalance and Fear of Falling: Comparing Urban and Rural Aging Communities - Nazari, Mahin; Rakhshani, Tayebeh; Khani Jeihooni, Ali; Bakht Abnoos, Abedin; Asadollahi, Abdolrahim (Current Aging Science, 2023)
Background: The relationship between environmental diversity and the health status of older adults has been less considered in studies. This study seeks to investigate the causal relationship among the environment, falling, fear of falling, and the imbalance of older adults in southern Iran in 2021. Objective: The investigation into the relationship between environmental pollution to the imbalance and fear of falling, especially in comparing urban and rural aging societies is the aim of current study. Methods: In a cross-sectional study, 489 older samples from rural and urban areas were chosen randomly and their experience of falling, fear of falling, imbalance, and IADL were examined. The ordinal and nominal logistic regression and ANOVA were performed using IBM-SPSS. Results: With a mean age of 71.8 (SD = 8.3), older participants have long time chronic disease (69.6%) and falling experience twice a year (42.7%). The values of effect size indicated the high effectiveness of settlement in explaining IADL, health situation, experience and fear of falling, and imbalance (Eta squared > 30). The odds ratio for being in the urban settlement was 5.51, indicating the imbalance score increased by approximately 5.52 times. Conclusion: Imbalance in older people leads to the fear and experience of falling. This imbalance is strongly influenced by the environment. Urban pollution can contribute to this problem. Future studies on aging need to focus on environmental pollution and diversity in the experience of falling and imbalance.
Keywords: Fear of falling